2020
DOI: 10.1002/eahr.500044
|View full text |Cite
|
Sign up to set email alerts
|

Research Participant Views regarding Qualitative Data Sharing

Abstract: We found no studies in the United States that explored research participants' perspectives about sharing their qualitative data. We present findings from interviews with 30 individuals who participated in sensitive qualitative studies to explore their understanding and concerns regarding qualitative data sharing. The vast majority supported sharing qualitative data so long as their data were deidentified and shared only among researchers. However, they raised concerns about confidentiality if the data were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 20 publications
(42 reference statements)
5
39
0
3
Order By: Relevance
“…The overwhelming majority of our respondents agreed to data sharing, which aligns with results from prior studies (Cummings et al, 2015;Kuula, 2011;Mozersky et al, 2020). Similarly, our respondents expressed that a desire to help and improve research were primary motivations for agreeing to data sharing, which mirrors the results of other research, both for qualitative and quantitative data (Mozersky et al, 2020;Shah et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…The overwhelming majority of our respondents agreed to data sharing, which aligns with results from prior studies (Cummings et al, 2015;Kuula, 2011;Mozersky et al, 2020). Similarly, our respondents expressed that a desire to help and improve research were primary motivations for agreeing to data sharing, which mirrors the results of other research, both for qualitative and quantitative data (Mozersky et al, 2020;Shah et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…The overwhelming majority of our respondents agreed to data sharing, which aligns with results from prior studies (Cummings et al, 2015;Kuula, 2011;Mozersky et al, 2020). Similarly, our respondents expressed that a desire to help and improve research were primary motivations for agreeing to data sharing, which mirrors the results of other research, both for qualitative and quantitative data (Mozersky et al, 2020;Shah et al, 2019). Among the small number of respondents who did not consent to data sharing, concern about confidentiality and how secondary researchers might use their data arose as major barriers to sharing, as Yardley et al (2014) found.…”
Section: Discussionsupporting
confidence: 77%
“…Interviews were audio-recorded and then transcribed verbatim by a professional transcription service. 4 , 13 …”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 In concurrent work, we explored the attitudes of qualitative researchers, data curators, institutional review board (IRB) members, and qualitative research participants regarding the barriers and benefits of QDS. 4 , 13 While attitudes toward QDS vary, there is broad willingness and support of QDS among stakeholder groups. The biggest barriers to QDS currently are lack of knowledge, resources, and algorithms and support software, to facilitate the deidentification of qualitative data so that it can be responsibly and ethically shared in a data repository.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation